Erythrocyte-Coated Nanoparticles Block Cytotoxic Effects of Group B Streptococcus β-Hemolysin/Cytolysin - Koo, Jenny; Escajadillo, Tamara; Zhang, Liangfang; Nizet, Victor; Lawrence, Shelley M. (Frontiers in Pediatrics, 2019)
Group B Streptococcus (GBS) emerged as a leading cause of invasive infectious disease in neonates in the 1970s, but has recently been identified as an escalating public health threat in non-pregnant adults, particularly those of advanced aged or underlying medical conditions. GBS infection can rapidly develop into life-threatening disease despite prompt administration of effective antibiotics and initiation of state-of-the-art intensive care protocols and technologies due to deleterious bacterial virulence factors, such as the GBS pore-forming toxin β-hemolysin/cytolysin (β-H/C). β-H/C is known to have noxious effects on a wide range of host cells and tissues, including lung epithelial cell injury, blood brain barrier weakening, and immune cell apoptosis. Neonatal and adult survivors of GBS infection are at a high risk for substantial long-term health issues and neurologic disabilities due to perturbations in organ systems caused by bacterial- and host- mediated inflammatory stressors. Previously engineered anti-virulence inhibitors, such as monoclonal antibodies and small molecular inhibitors, generally require customized design for each different pathogenic toxin and do not target deleterious host pro-inflammatory responses that may cause organ injury, septic shock, or death. By simply wrapping donor red blood cells (RBCs) around polymeric cores, we have created biomimetic “nanosponges.” Because nanoparticles retain the same repertoire of cell membrane receptors as their host cell, they offer non-specific and all-purpose toxin decoy strategies with a broad ability to sequester and neutralize various bacterial toxins and host pro-inflammatory chemokines and cytokines to attenuate the course of infectious disease. This proof-of-concept study successfully demonstrated that intervention with nanosponges reduced the hemolytic activity of live GBS and stabilized β-H/C in a dose-dependent manner. Nanosponge treatment also decreased lung epithelial and macrophage cell death following exposure to live GBS bacteria and stabilized β-H/C, improved neutrophil killing of GBS, and diminished GBS-induced macrophage IL-1β production. Our results, therefore, suggest biomimetic nanosponges provide a titratable detoxification therapy that may provide a first-in-class treatment option for GBS infection by sequestering and inhibiting β-H/C activity.